2013
DOI: 10.1183/09031936.00074413
|View full text |Cite
|
Sign up to set email alerts
|

Variability of hospital resources for acute care of COPD patients: the European COPD Audit

Abstract: Studies have suggested that larger hospitals have better resources and provide better care than smaller ones. This study aimed to explore the relationship between hospital size, resources, organisation of care and adherence to guidelines.The European COPD Audit was designed as a pilot study of clinical care and a survey of resources and organisation of care. Data were entered by clinicians to a multilingual web tool and analysed centrally. Participating hospitals were divided into tertiles on the basis of bed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
37
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(38 citation statements)
references
References 24 publications
1
37
0
Order By: Relevance
“…Moreover, the number of intubated patients after NIV failure was very small, indicating that NIV was a ceiling therapy for most of the cases who died after NIV. Reasons for delaying or withholding NIV are dependent on physicians' decisions, but may also be influenced by the availability of NIV and access to the intensive care unit (ICU) for COPD patients, as first reported by ROBERTS et al [14] and confirmed by this European COPD Audit [9]. This is alarming when guidelines recommend that NIV should be delivered in a dedicated setting and ICU admission should be considered in respiratory failure for COPD [16].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, the number of intubated patients after NIV failure was very small, indicating that NIV was a ceiling therapy for most of the cases who died after NIV. Reasons for delaying or withholding NIV are dependent on physicians' decisions, but may also be influenced by the availability of NIV and access to the intensive care unit (ICU) for COPD patients, as first reported by ROBERTS et al [14] and confirmed by this European COPD Audit [9]. This is alarming when guidelines recommend that NIV should be delivered in a dedicated setting and ICU admission should be considered in respiratory failure for COPD [16].…”
Section: Discussionmentioning
confidence: 99%
“…Both countries used audits to collect clinical data of patients hospitalised with COPD exacerbation, and the related standards of care and organisational resources. In 2010/11, the audit methodology was used for the first time in a European COPD Audit in 13 countries to investigate the variations of care and resources across Europe [8].The variability of resources across European hospitals in this COPD audit was substantial, but greater resources in larger hospitals did not guarantee better access to care and the standards of care as described in guideline recommendations were fulfilled in only 15.3% of patients across all hospitals [8,9].…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have shown large between‐hospital 4, 5, 6, 7, 8, 9 and between‐country 10 variations in resources, management and outcomes. A number of studies are consistent with our findings that the clinical aspect appears to be the most relevant of all potential determinants of in‐hospital mortality.…”
Section: Discussionmentioning
confidence: 96%
“…Thus, correct and standardised clinical care should be provided to these patients. However, previous studies have shown that there is significant variability in AECOPD processes of care and outcomes across hospitals 4, 5, 6, 7, 8, 9 and countries 10. The AUDIPOC study, a nationwide clinical audit on AECOPD conducted in Spain from 2008 to 2009 11, included 129 Spanish public general hospitals 12.…”
Section: Introductionmentioning
confidence: 99%
“…All in all, this data mining analysis allowed the identification of plausible molecular links between COPD and comorbid diseases, and showed that many of them are targets of the tobacco exposome 30 . Then, we extended this data mining analysis to real world data by using information gathered from two large COPD clinical audits [33][34][35][36][37] to study the clinical and molecular relationships between comorbidities in 5,447 patients hospitalized because of an exacerbation of COPD 38 . In these patients we constructed and compared their clinical diseasome (CD) and the molecular diseasome (MD).…”
Section: Systems Biology: What Does It Deliver?mentioning
confidence: 99%